The Impact Of Exchange Rate Misalignment And Volatility On Malaysian Trade Flows - Niaz Ahmad, Mohd Naseem (2007)

(untitled)
This study empirically examines the influence of real exchange rate behaviors, explicitly in term of its misalignment and volatility on the trade flows of a small fastgrowing economy, particularly Malaysia by employing Johansen multivariate errorcorrection model as well as autoregressive distributed lag (ARDL) to capture the estimates of the long-run and short-run relationships over the quarterly data for the period of 1991:1 to 2003:4. A measure of the quantitative proxy of the real exchange rate misalignment is constructed through the NATREX model while the volatility of real exchange rate is generated from the GARCH (1,1) model. It is particularly crucial because international trade played as main engine to generate and sustain economic growth for small open economies. A number of important conclusions can be drawn from the study. It is observed that the Malaysian real exchange rate was overvalued before the eruption of the Asian financial crisis in 1993-1997. After the crisis, the rate was undervalued in the mid 1997-2003. The rate was stable prior to the crisis, but was very volatile during the crisis period. The empirical finding shows that the Malaysia’s exports and imports are more sensitive to exchange rate misalignment throughout the sample-study period. In the meantime, exchange rate volatility appears to be most harmful to the Malaysia’s exports and imports in the post-sample period during the 1997 Asian financial crisis. On the other hand, the income effect provide a conducive condition to further boost Malaysia’s exports and imports as increase in the foreign and domestic income, respectively. For the price effect, Malaysia seems to offer a competitive price of export in pre-crisis period while Malaysia’s import is price inelastic through the sample period, where as a small open economy, Malaysia acts as a price taker in the international market. Nevertheless, the shift to a fixed or pegged exchange rate system is an appropriate measure as it reduced magnitude of the exchange rate misalignment and volatility (as computed through ATSSE and ATSCSD, respectively), where it may seem to be a successful case of crisis management in a small open dynamic economy, namely Malaysia.